Combined oxidation, deprotonation, and metal coordination of a redox-active guanidine ligand - Wild, Ute; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2015)
Abstract Guanidino-functionalized aromatic compounds (GFAs) are strong organic electron donors and redox-active ligands. The diversity of GFA chemistry results from reaction sequences that are triggered by their oxidation. This work reports on reactions of a new GFA compound, namely, 1,2,4,5-tetrakis(N,N?-dicyclohexylguanidino)benzene, with transition metals, and analyzes the interplay between GFA oxidation, coordination, and hydrogen-bond formation up to deprotonation. The reaction of the new GFA with [{PdCl(C3H5)}2] led to coordination and a coupled proton- and electron-transfer reaction.